Modulation of the mTOR Pathway by Curcumin in the Heart of Septic Mice - Bruna A. C. Rattis; Henrique L. Piva; Andressa Duarte; Frederico G. F. L. R. Gomes; Janaína R. Lellis; Danilo F. Soave; Simone G. Ramos; Antonio C. Tedesco; Mara R. N. Celes (MDPI AG, 2022)
mTOR is a signaling pathway involved in cell survival, cell stress response, and protein synthesis that may be a key point in sepsis-induced cardiac dysfunction. Curcumin has been reported in vitro as an mTOR inhibitor compound; however, there are no studies demonstrating this effect in experimental sepsis. Thus, this study aimed to evaluate the action of curcumin on the mTOR pathway in the heart of septic mice. Free curcumin (FC) and nanocurcumin (NC) were used, and samples were obtained at 24 and 120 h after sepsis. Histopathological and ultrastructural analysis showed that treatments with FC and NC reduced cardiac lesions caused by sepsis. Our main results demonstrated that curcumin reduced mTORC1 and Raptor mRNA at 24 and 120 h compared with the septic group; in contrast, mTORC2 mRNA increased at 24 h. Additionally, the total mTOR mRNA expression was reduced at 24 h compared with the septic group. Our results indicate that treatment with curcumin and nanocurcumin promoted a cardioprotective response that could be related to the modulation of the mTOR pathway.